2020
DOI: 10.15587/1729-4061.2020.212018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the shape formation of parts with a flange and an axial protrusion in the process of combined aligned radial-direct extrusion

Abstract: Using the calculation schemes CS-1 (with the presence of a trapezoid module) and CS-1a (with rectangular kinematic modules) has been proposed for the process of the combined radial-direct extrusion of parts with a flange and an axial protrusion. The application of a trapezoidal kinematic module allows the description of the characteristic regions of metal flow, close to the actual course of the process based on the distorted coordinate grids. On the basis of the energy method, the values of the reduced deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this case, constructing a new kinematic module typically allows it to be used not only for one particular estimation scheme or process but for a suite of different schemes where it can serve as their element. At the same time, an important role belongs to the peculiarities of MKM application for modeling the processes of combined extrusion in accordance with the classification of basic strain sites (SSs): sequential, connected, combined, transit, and combined [16,21,24,31,32].…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, constructing a new kinematic module typically allows it to be used not only for one particular estimation scheme or process but for a suite of different schemes where it can serve as their element. At the same time, an important role belongs to the peculiarities of MKM application for modeling the processes of combined extrusion in accordance with the classification of basic strain sites (SSs): sequential, connected, combined, transit, and combined [16,21,24,31,32].…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…For processes with connected SS, the main task is to find the position of the boundary of two adjacent SSs with one degree of freedom of flow of metal [31] (Fig. 1, right pattern, SS-II-1 and SS-II-2).…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…It was concluded that with an increase in the angle of inclination of the working edge of the tool, the uniformity of the distribution of deformations increases. However, an increase in crimping helps reduce the surface roughness of the workpiece but this may result in destruction of the product [17].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Methods of sequential radial-longitudinal extrusion are designed to obtain hollow parts. There are two variants of this method: with expansion (scheme 5 and 6) [5] and with reduction of metal during its radial flow (scheme 7) [4,6].…”
Section: Literature Reviewmentioning
confidence: 99%